Will the U.S. and EU Telecommunications Policies Converge? A Survey - Ingo Vogelsang (Center for Economic Studies and ifo Institute (CESifo), 2014)
Currently, U.S. and EU telecommunications policies differ in many respects. For example, wholesale access to local loops is largely deregulated in the U.S. but continues to be regulated in the EU. Or, the U.S. has an elaborate universal service policy with a set of universal service funds and specific policies for high-cost regions and low-income users, while universal service policies in the EU are much more sporadic. Will the forceful technical and market developments that are associated with IP convergence, next generation access (NGA) and mobile broadband (4G) lead to a convergence of telecommunications policies in the U.S. and EU? Based on a survey of the relevant U.S. and EU related economics literature the current paper addresses this issue for the five policy areas of interconnection, wholesale loop access, net neutrality, spectrum policy and universal service. While IP convergence and the spread of 4G are likely to enhance policy convergence, NGA could have a different effect, because the penetration of and the competitive properties of NGA depend crucially on legacy infrastructures that differ between the two continents.
Keywords: L43; L86; L96; L98; 330